Effects of Service Recovery Expectation and Recovery Justice on Customer Citizenship Behavior in the E-Retailing Context - Zhu, Tingting; Liu, Beilei; Song, Mengmeng; Wu, Jinnan (Frontiers in Psychology, 2021)
Customer citizenship behavior in online shopping environment is vital to the success of e-retailers. However, it is unclear whether and how service recovery expectation and recovery justice predict customer citizenship behavior in e-retailing settings. Grounded on the expectation confirmation theory and social exchange theory, this study examined the influence of service recovery expectation and recovery justice on customer citizenship behavior with a serial mediation of recovery expectation confirmation and post-recovery satisfaction. A total of 774 samples from e-shoppers with most impressive (N=401) and most recent (N=373) service recovery experience were collected to test the hypotheses using structural equation modelling and bootstrapping procedures. This study reveals that service recovery expectation has a negative impact on recovery expectation confirmation, while recovery justice positively affects recovery expectation confirmation, which is further positively correlated with post-recovery satisfaction and customer citizenship behavior. Moreover, recovery expectation confirmation and post-recovery satisfaction play a serial mediation in the relationship between service recovery expectation and recovery justice, and customer citizenship behavior. Our study contributes to the growing body of customer citizenship behavior literature by offering an alternative perspective (i.e., service recovery) to understand what encourage or impede customer citizenship behavior, and expands service recovery literature by combining service recovery expectation and recovery justice into a framework and revealing the expectation-confirmation mechanism through which they influence post-recovery satisfaction in online shopping settings.